Advancing Genome-Resolved Metagenomics beyond the Shotgun - Malmstrom, Rex R. (mSystems, 2019)
Exploration of environmental microbiomes has shed light on the ecological and evolutionary principles at play in natural ecosystems and has been further accelerated through the reconstruction of population genomes to provide genome-centric context. Yet technical challenges with traditional shotgun metagenomics remain for computationally intense short-read assembly, strain heterogeneity within communities, and depth of coverage required for low-abundance microbes. In this Perspective, we highlight three main avenues for promising future developments, including coupling stable isotope probing and genome-resolved metagenomics, applying fluorescence-activated cell sorting approaches to target mini-metagenomes within a larger community, and utilizing single-molecule long-read and synthetic long-read technology to link mobile elements to host microbial cells. These developments on the horizon will undoubtedly advance genome-resolved metagenomic approaches and enable a better understanding of uncultivated microbes in their natural environments.